2020
DOI: 10.4314/ovj.v9i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler to investigate superficial digital flexor tendinopathy in the horse

Abstract: Background: Recent advances in tendinopathy research have focused on tendon vascularization detected with Color Doppler (CD) ultrasound. The use of CD has also been described in horses in a study on chronic lesions of superficial digital flexor tendon and suspensory ligament. Aim: The aim of this study was to investigate the occurrence and distribution of power Doppler (PD) signal in horses with superficial digital flexor tendinopathy. Methods: Twenty-five horses with tendinopathy were included and 10 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Another benefit of ultrasound, while not utilized in this study, is that ultrasound allows the use of Doppler interrogation to help assess the vascularity of tendon lesions. The exact significance of increased Doppler signal still requires additional research, but it can be useful to help identify or confirm lesions and assess for active increased vascularity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Another benefit of ultrasound, while not utilized in this study, is that ultrasound allows the use of Doppler interrogation to help assess the vascularity of tendon lesions. The exact significance of increased Doppler signal still requires additional research, but it can be useful to help identify or confirm lesions and assess for active increased vascularity [32].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the study was the use of grayscale B-mode ultrasonography only, as this modality is less sensitive than color doppler or power doppler techniques in detecting blood vessels. However, previous studies have reported that power Doppler signals indicating neovascularization are not detected in structures such as suspensory ligament branches and the superficial digital flexor tendon when there are no abnormal findings detected by B-mode ultrasonography [ 10 , 26 ]. The fact that power Doppler signals were also seen in suspensory ligament branches of sound limbs albeit with abnormal B-mode ultrasonographical findings [ 26 ], complicates the interpretation of the clinical relevance of such findings and highlights the need for histopathological confirmation of disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, neovascularization of the patellar tendon identified by power doppler ultrasonography has been identified as a more specific diagnostic indicator of clinical patellar tendinopathy [ 7 ], most likely as nociceptive nerve fibers accompany the blood vessel ingrowth [ 9 ]. Power doppler ultrasonography has also been used for detecting neovascularization in superficial digital flexor tendinopathy in horses [ 10 ] and could potentially be useful for diagnosing PL lesions. However, whereas the normal vascular architecture of the equine superficial digital flexor tendon has been described [ 11 ], such information is lacking for the equine PLs.…”
Section: Introductionmentioning
confidence: 99%
“…La ultrasonografía con Doppler DPI ha demostrado ser útil para la detección de la microvasculatura en los tendones de Aquiles y de la rótula en el hombre 19,20 . Los primeros informes que describen la aplicación de la ultra-sonografía Doppler para la evaluación de las ramas del ligamento suspensorio equino y la tendinopatía del SDF muestran resultados prometedores 21,22 .…”
Section: Discussionunclassified